Identification of β-cycloidal-derived mono-carbonyl curcumin analogs as potential interleukin-6 inhibitor to treat wound healing through QSAR, molecular docking, MD simulation, MM-GBSA calculation - Forid, Md Shaekh; Patil, Rajesh B.; Roney, Miah; Huq, A. K. M. Moyeenul; Mohd Hamzah, Mohd Nasir; Mohd Fadhlizil Fasihi, Mohd Aluwi; Muhammad Saupi, Azuri; Wan Maznah, Wan Ishak (Taylor & Francis, 2024)
Interleukin-6 (IL-6) is a cytokine that involved in the different phases of wound healing. It is responsible for promoting inflammation, regulating tissue repair scar formation, stimulating the production of extracellular matrix components and recruiting immune cells to the wound site. Therefore, suppressing IL-6 is beneficial for wound healing. However, no small molecules are currently available in the market against the IL-6. As a result, this research gap motivates us to find a potential inhibitor. This study aimed to investigate the wound healing potential of novel β-cycloidal-derived mono-carbonyl curcumin analogs reported in the literature through screening a series of computational studies. The calculated pIC50 value of 18 compounds (below 10) showed that all compounds may have potential therapeutic efficacy. Molecular docking studies revealed that compound C12 (−45.6044 kcal/mol) bound most strongly in the active site of IL-6 compared to the FDA-approved drug clindamycin (−42.3223). The Molecular Dynamic (MD) simulation displayed that lead compound C12 had the highest stability in the active site of IL-6 compared to the reference drug clindamycin. Furthermore, MMGBSA results indicated that C12 (−20.28 kcal/mol) had the highest binding energy compared to clindamycin (−8.36 kcal/mol). The ADMET analysis predicted that C12 are favourable for drug candidates. This study recommended compound C12 as a lead IL-6 inhibitor for future testing and development as therapeutics for wound healing.